(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The combustion chamber was developed in the laboratories of the University of Babylon for the purpose of conducting the study to measure the speed of turbulent combustion, where four high-speed impellers were installed symmetrically in the vicinity of the combustion chamber, where they formed a homogeneous swirling disorder. Iraqi liquefied petroleum, where the percentage of ammonia gas was (10) using the Schlieren imaging system to photograph the growth of the flame under conditions of initial pressure (100, 200, 300) kPa and the coefficient of equivalence (0.8 , 1 ,1.3 ), and the image was processed and analyzed using the MATLAB program, and the speed of turbulent combustion was calculated depending on the average diameter of the combustion flame due to the irregular diameter As a result of the turbulence, we obtained a laminar combustion speed whose value was (28.64 cm/sec)and at an initial pressure of an amount and an equivalence ratio, and at the same equivalence ratio and an initial pressure of an amount and the same conditions for the same equivalence ratio, the turbulent combustion speed was (49.11 cm/sec), and this explains the effect of turbulence by increasing the combustion speed